The Effect of Digital Marketing on Consumer Purchase Intention for Ornamental Plants in Online Markets: Evidence from Batu City, Indonesia - Dwie Retna Suryaningsih; Mochammad Thohiron; Sukian Wilujeng (Asia Pacific Journal of Business Economics and Technology, 2026)
This study aims to analyze the effect of digital marketing on consumers' purchase intention for ornamental plants in online markets in Batu City. The research employed a quantitative approach using a survey method involving 50 respondents selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics software. The results indicate that digital marketing has a positive and significant simultaneous effect on consumers' purchase intention. Partially, the variables of Social Media Marketing, Online Advertising, Electronic Word of Mouth (e-WOM), and Marketplace Marketing have a positive and significant effect on consumers' purchase intention, whereas Content Marketing does not have a significant effect. Among the independent variables, Marketplace Marketing exerts the strongest influence on consumers' purchase intention. The coefficient of determination (Adjusted R²) of 0.642 indicates that 64.2% of the variation in consumers' purchase intention can be explained by the digital marketing variables included in the model, while the remaining 35.8% is explained by other factors outside the scope of this study. The findings are expected to provide valuable insights for ornamental plant business owners in developing more effective digital marketing strategies to enhance consumers' purchase intention and improve business competitiveness in online markets.